Formulasi Sediaan Tablet Dan Evaluasi Dari Jenis Zat Aktif Dengan Metode Granulasi Basah - Jaida Rahma; Alya Puspita Dewi; Septia Miranti; Hendri Anugrah Wibowo; Nabila Syifa Firdaus (Jurnal Sains Farmasi Dan Kesehatan, 2024)
This study aims to understand how the wet granulation technique can affect the physical quality and the effectiveness of active ingredient release in tablets. In this review, various types of active ingredients will be analyzed to evaluate how their chemical and physical properties, such as solubility, compressibility, and stability, influence the resulting tablet formulation. Wet granulation was chosen due to its ability to improve the flow, compressibility, and stability of the mixture of active ingredients and excipients, resulting in tablets with better quality. To achieve this objective, the study uses a Systematic Literature Review (SLR) approach, which gathers and analyzes relevant literature related to tablet formulations with active ingredients using wet granulation. The results of the review show that wet granulation is effective in improving the physical quality of tablet and granule preparations. Wet granulation can enhance flow, compressibility, and active ingredient release control, although it has drawbacks, such as high costs and multiple stages that require validation. Increasing the concentration of gelatin in the tablet formulation of Eugenia polyantha extract improved the physical strength and dissolution rate of the tablets. Similarly, research on acetaminophen demonstrated that wet granulation produces tablets with physical qualities that meet the required standards for tablet physical testing. Finally, this study shows that Tectona grandis leaf extract can be formulated into granules with optimal quality that meets the physical evaluation criteria. Overall, wet granulation has proven to be effective in improving the quality and release of active ingredients in tablets and granules, with the selection of appropriate materials and concentrations greatly affecting the final formulation results.